Coastal Deposits: Environmental Implications, Mathematical Modeling and Technological Development (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue on "Coastal Deposits: Environmental Implications, Mathematical Modeling, and Technological Development" includes seven high-quality, innovative research papers dealing with many scientific aspects regarding the coast, through mathematical modelling and innovative techniques in the study and preservation of the coastline from erosion, such as coastal watch camera installations, remote sensing, the use of biocementation, or analytical techniques, to assess incompatibilities in the sustainable use of the coast, including worrying issues as pollution of the marine environment and ecosystem deterioration.